Synthesis of the Cysteine Protease Inhibitors CPI-2081a and CPI-2081b Using a Controlled SPPS Byproduct Forming Reaction - Heapy, Amanda M.; Dragunow, Mike; Brimble, Margaret A. (Synlett, 2013)
An efficient first synthesis of the cysteine protease inhibitors CPI-2081a and CPI-2081b is described. These naturally occurring penta-peptides exhibit extensive amino acid modifications including N-terminal acylation, S-tert-butylation and C-2 p-hydroxybenzyl alkylation of the tryptophan indole ring in CPI-2081b. Both compounds were synthesised by using Fmoc SPPS. In the case of CPI-2081b a SPPS side reaction was optimized to allow straightforward synthetic access to this p-hydroxybenzylated tryptophan-containing natural product.
Keywords: natural products; solid-phase synthesis; peptides; cysteine protease inhibitor